The gendered perspective of cyberbullying: The case of a rural University in Limpopo - Memory Mabika (Communicare)
The rapid advancement of Information and Communication Technologies (ICTs) has heightened misuse of internet-based technologies by young people. Besides increased integration due to availability and access to mobile communication technologies, students today indulge in cyberbullying where they harass, insult and stalk each other. Scholars have researched extensively on cyberbullying in institutions of higher learning globally and how victims try to cope with the problem. However, there is a dearth of literature on the gendered perspective of cyberbullying in institutions of higher learning in Southern Africa. Using the Social Information Processing Theory, the study examined the phenomenon of cyberbullying at a rural university in South Africa. The key questions of the study were: How do male and female victims perceive cyberbullying? How do male and female victims react to cyberbullying? Does cyberbullying have the same effects on students of different gender? Data were collected using semi-structured interviews and questionnaires targeted at male and female victims of cyberbullying at University of Venda. Findings revealed inconsistencies in how male and female victims perceived and reacted to cyberbullying.